Exploring Language Trends on TikTok: Impacts on Indonesian Communication - Lisa Ananda Wijaya Lisa; Yundi Fitrah; Maizar Karim (Universitas Islam Negeri Palopo, 2025)
This study explores the emerging language trends on the TikTok platform and their impacts on communication in Indonesia. As TikTok continues to grow as a dominant social media platform, understanding language adaptation and usage among its users becomes increasingly significant. This research employs a qualitative method through content analysis of high-interaction TikTok videos to examine linguistic patterns. The findings reveal that slang, code-switching, and local cultural elements play a crucial role in shaping communication styles. Slang expressions, often derived from youth culture and internet memes, are widely used to create a sense of identity and belonging among users. Code-switching between Indonesian, English, and regional languages is also prevalent, reflecting the dynamic and multilingual nature of digital communication. Additionally, the incorporation of local cultural elements, such as traditional phrases and dialects, enriches interactions, making them more relatable to specific audiences. These linguistic trends contribute to the evolution of digital communication, influencing how Indonesian youth express themselves and engage with online communities. The study highlights the significance of TikTok as a platform where language is not only a tool for interaction but also a means of cultural expression and identity formation. By analyzing these trends, this research provides valuable insights into the shifting communication patterns in Indonesia’s digital landscape.